Effect of Flexible Working Arrangement on Employee Performance: Mediating Role of Work Engagement and Supervisor Support in Indonesia Digital Startup - Pradipta, Hana Angelia; Martdianty, Fanny (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
To cope with unprecedented change, remote work provides organizations with an option for a flexible work arrangement (FWA) environment to maintain performance during turbulent situations; recent research has reported that the practice has gained popularity among employees. It is essential to deepen our knowledge about the performance of employees in the context of FWA because the results of previous studies need to be more consistent. This study examines the mediating role of work engagement and supervisor support on the relationship between FWA and team member performance. The data were collected from 316 employees working in digital startup companies in Indonesia. The research is analyzed using structural equation modeling (SEM). The results show that work engagement and supervisor support as mediating roles affect the relationship between FWA and employee performance. The results found work engagement as a mediating relationship between supervisor support and employee performance. Supervisory support in the form of support for employees makes them feel more valued, and it affects job performance. High work involvement improves employee performance while practicing flexible work arrangements. Keywords: employee performance, digital startup, flexible, supervisor support, work arrangement, work engagement